REPORT ON AIRCRAFT CABIN AIR QUALITY (Tufts Archival Research Center, 2007)
Missing Attachments; Memorandum from Sam Chilcote to the executive committee regarding the release of the Department of Transportation Study on Aircraft Cabin Air Quality. Comments that legislation may surface as a result of these types of studies and the Tobacco Institute may have to take action to prevent such decisions.